Tetracycline-resistant L-forms isolated from an antibiotic-susceptible strain of Listeria monocytogenes. - Schmitt-Slomska, J (1982)
A tetracycline-susceptible strain of Listeria monocytogenes type 4b was converted to stable L-forms by penicillin. L-form variants resistant to tetracycline were then selected from a predominantly tetracycline-susceptible L-form population on plates containing penicillin and increasing concentrations of tetracycline. The origin of tetracycline-resistant L-forms from the parent Listeria strain was confirmed biochemically, by immunofluorescence, and by polyacrylamide gel electrophoresis. Scanning and transmission electron microscopy confirmed the typical L-form structure and the complete lack of cell wall in both L-form strains. The level of [3H]tetracycline uptake was lower in tetracycline-resistant than in susceptible cells.